An enzyme from lupin seeds forming alanine derivatives of cytokinins - Entsch, B.; Parker, C. W.; Letham, D. S.
A new enzyme, which catalyses the conversion of the cytokinin zeatin to the alanine conjugate lupinic acid, has been partly purified from developing lupin seed (Lupinus luteus). Paired-ion, reverse phase HPLC was adapted to analyse the enzyme reaction quantitatively. The enzyme used O-acetyl-l-serine as the source of the amino acid residue, and it interacted with substrates in a ping pong bi bi mechanism. A number of adenine derivatives served as substrates, but preference was shown for compounds with high cytokinin activity. The possible role of the enzyme, tentatively called B-(9-cytokinin)alanine synthase or lupinic acid synthase, in the regulation of hormone activity is discussed
Keywords: LUPINUS LUTEUS; LEGUMINOSAE; CYTOKININ METABOLISM; ENZYME FORMING ALANYL CONJUGATES; PURIFICATION